2010
DOI: 10.1371/journal.pone.0008977
|View full text |Cite
|
Sign up to set email alerts
|

Agroinfiltration Reduces ABA Levels and Suppresses Pseudomonas syringae-Elicited Salicylic Acid Production in Nicotiana tabacum

Abstract: Background Agrobacterium tumefaciens strain GV3101 (pMP90) is widely used in transient gene expression assays, including assays to study pathogen effectors and plant disease resistance mechanisms. However, inoculation of A. tumefaciens GV3101 into Nicotiana tabacum (tobacco) leaves prior to infiltration with pathogenic and non-host strains of Pseudomonas syringae results in suppression of macroscopic symptoms when compared with leaves pre-treated with a buffer control.Methodology/FindingsTo gain further insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…However, despite of inducing chlorosis, T. evansi protein Te84 did not suppress PR1 or PR4 expression, which suggests that there is no direct causal relationship between the chlorosis phenotype and the suppression of SA‐related defenses. Moreover, chlorosis during agroinfiltration in N. benthamiana usually coincides with stronger, not weaker, SA responses (Rico et al ., ). Taken together, chlorosis may be indicative, yet not fool‐proof, as a visible phenotype for selecting candidate herbivore effector proteins.…”
Section: Discussionmentioning
confidence: 97%
“…However, despite of inducing chlorosis, T. evansi protein Te84 did not suppress PR1 or PR4 expression, which suggests that there is no direct causal relationship between the chlorosis phenotype and the suppression of SA‐related defenses. Moreover, chlorosis during agroinfiltration in N. benthamiana usually coincides with stronger, not weaker, SA responses (Rico et al ., ). Taken together, chlorosis may be indicative, yet not fool‐proof, as a visible phenotype for selecting candidate herbivore effector proteins.…”
Section: Discussionmentioning
confidence: 97%
“…1C). Therefore, induction of ipt expression at the site of infection is highly effective in preventing disease development. Since it has been shown that A. tumefaciens may interfere with symptom development after P. syringae infection (Rico et al, 2010), we employed two additional transgenic approaches, which confer ectopic elevation of endogenous CK levels independent of prior A. tumefaciens infiltration, to confirm the specificity of the observed CK effect. First, we used SAG12:ipt transgenic tobacco plants expressing the ipt gene under the control of a senescence-induced promoter (Gan and Amasino, 1995).…”
Section: Induction Of Endogenous Ck Biosynthesis In Tobacco Leaves Enmentioning
confidence: 99%
“…Leaves were observed for symptom development and bacterial growth was measured over the subsequent 3 days. Infiltrating leaves with Agrobacterium has been shown to induce immune responses that inhibit the growth of Ps in subsequent inoculation (21)(22)(23). We therefore compared the growth of Ps in leaves transiently expressing When we measured bacterial load in leaves expressing PL1, Ps titres were 5-log units lower than in non-agroinfiltrated control leaves and crucially 3-log units lower than in leaves expressing GFP ( Fig.…”
Section: Pl1 Has a Narrow Killing Spectrummentioning
confidence: 99%